2010
DOI: 10.1038/sc.2009.186
|View full text |Cite
|
Sign up to set email alerts
|

Transanal irrigation in myelomeningocele children: an alternative, safe and valid approach for neurogenic constipation

Abstract: Study design: A total of 60 children with myelomeningocele referred to Spina Bifida Center of Rome (31 boys and 29 girls; aged 8-17 years) were treated with transanal irrigation for three months. Objective: To investigate whether transanal irrigation is a valid and alternative approach for neurogenic constipation in children with myelomeningocele. Methods: A questionnaire on bowel disturbances, quality of life and side effects was completed before the beginning and at the termination of the study. Setting: Ita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
93
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(97 citation statements)
references
References 20 publications
3
93
0
1
Order By: Relevance
“…Some of the studies administered questionnaires to collect data on reported clinical symptoms, 4-9 Neurogenic Bowel Dysfunction Scale, 10,11 quality of life 5,10,11 and patient satisfaction Likert scales. 5,10,12 Only the Neurogenic Bowel Dysfunction Scale is a validated instrument (in adult patients), the other questionnaires used in the reported studies were locally developed and non-validated. There was a general lack of information within the papers on who completed the questionnaires.…”
Section: Details Of the Included And Excluded Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Some of the studies administered questionnaires to collect data on reported clinical symptoms, 4-9 Neurogenic Bowel Dysfunction Scale, 10,11 quality of life 5,10,11 and patient satisfaction Likert scales. 5,10,12 Only the Neurogenic Bowel Dysfunction Scale is a validated instrument (in adult patients), the other questionnaires used in the reported studies were locally developed and non-validated. There was a general lack of information within the papers on who completed the questionnaires.…”
Section: Details Of the Included And Excluded Studiesmentioning
confidence: 99%
“…There was a general lack of information within the papers on who completed the questionnaires. The majority of questionnaires appeared to be completed by parents either within the clinical setting as part of the child's normal health care follow-up [9][10][11] or over the telephone. 4,5,12,13 Several of the studies reported data collected retrospectively from medical case notes 6,13,14 or reported findings based on data without it being stated how data had been obtained.…”
Section: Details Of the Included And Excluded Studiesmentioning
confidence: 99%
See 3 more Smart Citations